Reliability and Validity of the Korean Version of the General-Food Craving Questionnaire-Trait for Children - Jeong, Jo-Eun; Jung, Dong-Jin; Kwak, Minjung; Yang, Hae Kyung; Lim, Sun-Young; Lee, Jin-Hee; Yoon, Kun-Ho; Kim, Dai-Jin (Psychiatry investigation, 2017)
The General-Food Craving Questionnaire-Trait (G-FCQ-T) is a validated, assessment scale for food craving. The aim of this study was to measure its reliability and validity for Korean children. A total of 172 children (94 boys and 78 girls) were selected to fill out a set of questionnaires, including the G-FCQ-T, the Children's version of the Dutch Eating Behavior Questionnaire (DEBQ-C), and the Three-Factor Eating Questionnaire (TFEQ) in the Korean language. The internal consistency (Cronbach's alpha=0.933) and test-retest reliability (r=0.653) were satisfactory. The G-FCQ-T showed a significantly positive correlation with the DEBQ-C (r=0.560) and the TFEQ (r=0.397). The optimum cutoff score of the G-FCQ-T set by Receiver Operating Characteristics analysis was 51, with sensitivity and specificity of 0.833 and 0.825, respectively, for children. The G-FCQ-T showed good reliability and validity for assessing food craving for children and could become a practial instrument in clinical and research settings.